Web site as a strategy in the education for sustainability - Dávila Sanabria, Doris Teresa; Galvis Álvarez, Aura Cecilia; Vivas Granados, Rolando (Universidad Pedagógica y Tecnológica de Colombia, 2015)
In this paper the theoretical and methodological aspects in creating learning environments through the design and the implementation of a website to support research processes conducted in the school vegetable garden are presented. The methodological design was framed in the participatory action research with education and teaching strategies based on the use of information and communication technology (ICT), generating along with children and parents, learning environments that are constitute as tools in teaching education for sustainability.